Association of Autonomic Activation with traumatic reminder challenges in posttraumatic stress disorder: A co‐twin control study. (12th August 2022) - Perez Alday, Erick A.; Da Poian, Giulia; Levantsevych, Oleksiy; Murrah, Nancy; Shallenberger, Lucy; Alkhalaf, Mhmtjamil; Haffar, Ammer; Kaseer, Belal; Ko, Yi‐An; Goldberg, Jack; Smith, Nicholas; Lampert, Rachel; et al.
Abstract: Post‐traumatic stress disorder (PTSD) has been associated with cardiovascular disease (CVD), but the mechanisms remain unclear. Autonomic dysfunction, associated with higher CVD risk, may be triggered by acute PTSD symptoms. We hypothesized that a laboratory‐based trauma reminder challenge, which induces acute PTSD symptoms, provokes autonomic dysfunction in a cohort of veteran twins. We investigated PTSD‐associated real‐time physiologic changes with a simulation of traumatic experiences in which the twins listened to audio recordings of a one‐minute neutral script followed by a one‐minute trauma script. We examined two heart rate variability metrics: deceleration capacity (DC) and logarithmic low frequency (log‐LF) power from beat‐to‐beat intervals extracted from ambulatory electrocardiograms. We assessed longitudinal PTSD status with a structured clinical interview and the severity with the PTSD Symptoms Scale. We used linear mixed‐effects models to examine twin dyads and account for cardiovascular and behavioral risk factors. We examined 238 male Veteran twins (age 68 ± 3 years old, 4% black). PTSD status and acute PTSD symptom severity were not associated with DC or log‐LF measured during the neutral session, but were significantly associated with lower DC and log‐LF during the traumatic script listening session. Long‐standing PTSD was associated with a 0.38 (95% confidence interval, −0.83, ‐0.08) and 0.79 (−1.30, ‐0.29) standardized unit lower DC and log‐LF, respectively, compared to no history of PTSD. Traumatic reminders in patients with PTSD lead to real‐time autonomic dysregulation and suggest a potential causal mechanism for increased CVD risk, based on the well‐known relationships between autonomic dysfunction and CVD mortality. Abstract : Our study employed an innovative laboratory trauma recall challenge to examine the acute impact of PTSD symptoms on autonomic physiology in male veteran twins. We found evidence that PTSD leads to real‐time pathological effects on the autonomic nervous system such as vagal withdrawal. Our findings provide direct evidence to a causal mechanism linking PTSD to heart disease by comparing PTSD discordant twin brothers.